(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The study objectives were to explore the climate changeimpacts experienced based on the perception of rural households and toexplain the adaptation strategies for rural households. Primary data werecollected using structured interviews, key-informant interviews and fieldobservations. The secondary data were collected from reports. Randomsampling technique was applied to select 200 forest-dependenthouseholds in Um-Rawaba locality (100 households) and SheikanLocality (100 households) in North Kordofan. The data were analyzedusing the SPSS statistical package. Descriptive statistics was used toidentify dominant responses between households. The study resultsrevealed that the households influenced by local climate change based ontheir perceptions. The main adaptation strategies by the households wereassets selling, saving, reliance on social relations, feeding on wild plants,wild fruits, wild animals; and temporary migration.